2019-LB: The Characteristic Activity of Regulatory B Cells during the Occurrence and Development of Insulin Resistance - WEI, LINGLING; ZHANG, LIJIE; MA, YAN; ZHAO, DONG; YANG, LONGYAN (Diabetes (New York, N.Y.), 2024)
Introduction & Objective: To investigate the aberrant distribution and clinical relevance of regulatory B cells (Bregs) subsets in the peripheral blood of individuals with different levels of insulin resistance (IR). Methods: A cohort of 124 subjects were divided into five groups according to their insulin resistance index (HOMA-IR) and diabetes diagnosis. The groups comprised HOMA-IR<3 (IR- without T2DM), HOMA-IR<3 (IR- with T2DM), 3≤HOMA-IR<6 (IR+ without T2DM), 3≤HOMA-IR < 6 (IR+ without T2DM) and HOMA-IR≥6 (IR++ with T2DM). Peripheral blood samples were collected from each group, the percentages of CD19+CD24+CD27+ and CD19+CD24+CD38+ Bregs and the levels of IL-2, IL-4, IL-6, IL-10, IL-17, TNF-α, IFN-γ were detected by flow cytometry and flow microsphere matrix method. Additionally, the cytokines levels were validated through ELISA. The activation of Bregs and the production of IL-10 among different groups were analyzed. Spearman correlation analysis was used to analyze the correlation between Bregs activation rate and IR degree. Results: The results showed that the levels of CD19+CD24+CD27+ and CD19+CD24+CD38+ cells were increased whether in IR+ without or with T2DM groups compared to the IR- group, with the most significant increase observed in the IR++ with T2DM group. Moreover, the plasma levels of IL-6, IL-10, IL-17, TNF-α and IFN-γ in the IR+ group were higher than those in the IR- group. The expression and activation level of Bregs were positively correlated with the severity of IR in T2DM. Conclusion: These results suggest that the increase level of Bregs is closely related to the severity of IR, highlighting the potential significance of Bregs in the clinical progression of Type 2 Diabetes Mellitus (T2DM) and its associated insulin resistance.